Gay Representation in Boy Meets Boy Movie by Daniel Lopez Sanchez - liawijaya, jefry; Anggraeni, Diana; Sigalingging, Bob Morison (Universitas Muhammadiyah Lampung, 2024)
Currently, illicit relationships such as those of same-sex couples have special symbols that they use as their identity. These symbols are created by their community. We can see directly and analyse their community’s symbols through movies. One of them is the gay movie that this research examined,